China's governance reform from 1978 to 2008 - Yu Keping (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2008)
This paper systematically examines the dominant processes and key issues of China's governance reforms over the last 30 years since the start of the reform and opening policies. It argues that the main thrust of China's governance reforms is the shift from monistic governance to pluralist governance, from centralization to decentralization, from rule of man to rule of law, from regulatory government to service-oriented government, and from intra-party democracy to people's democracy. This paper argues further that the focus of China's governance reform includes ecological balance, social justice, public service, social harmony, government cleanness, government innovation, intra-party democracy, grassroots democracy, etc. The variables of governance reform in China are social and economic development, the logic of political development, influence of new political culture and impacts of globalization. After persistent efforts in the past three decades, this paper contends that in China a unique governance model is emerging which is destined to democracy, rule of law, justice, accountability, transparency, cleanness, efficiency and harmony.
Keywords: 330; governance; democracy; political reform; governance model; government innovation; Politische Reform; Governance-Ansatz; Verwaltungsreform; China